Les outils de l'analyse fonctionnelle dans les pratiques enseignantes en technologie - MARJOLAINE CHATONEY; FABRICE GUNTHER; FATMA SAÏD (Metaichmio Publications, 2016)
The study of technical systems is central to technological education. It allows us to understand the complexity of the systems in their pluri-technical dimension. In education, it generally leans toward approaches of analysis functions, structure or behavior. Different tools are associated with these methods. The implementation of functional analysis from an industrial origin focuses on several problems: the problem of transferring industrial tools to technological education, specifically concerning the knowledge involved and the references, and the problem of appropriating and transforming these tools into artifacts for teaching. The purpose of this study, which is part of a larger research, is to identify and characterize the use of functional analysis in the declared practices of teachers in secondary schools. Using a survey, we analyze teachers' knowledge and practices regarding certain tools of functional analysis. We show that the teachers, even though they use these tools widely in secondary schools, do not claim expertise in using them. By categorizing the teachers and their responses, we try to highlight the main difficulties and find some clues that prevent functional analysis from becoming a generic method to study technical systems and becoming a constant part of technological teaching at all school levels.